ANALISIS KUALITAS PRODUKSI APEL PADA DESA TUTUR KABUPATEN PASURUAN - Alfiyah, Siti Nailul (Department of Management, 2018)
This research aims to know the quality of Apple production in Tutur Village Regency Pasuruan. By grouping into three groups, group with 0-5 apple farmer, group with 6-10 apple farmer, and group of more than 10 apple farmer. The population in this research and the entire manager and owner of the garden that is as much as 40 respondents. Data analysis used in this study is the range of the scale. Based on the results of the research and the discussion it can be concluded that: 0-5 apple farmer in which tenants are comprised of variable focusing on customers, continuous improvement, categorized well, while variable obsession to quality, involvement and empowerment of employees, categorized enough. 6-10 apple farmer grouping consisting of variable focusing on customers and variable obsession to quality categorized well, whereas continuous improvement, employee involvement and empowerment, categorized enough. Grouping more than 10 farmers apple farmer consisting of variable focusing on customers, variable obsession to quality, continuous improvement, employee involvement and empowerment, categorized either.